Toward characterizing solutions to complex programming problems involving fuzzy parameters in constraints - Hamiden Khalifa; Dragan Pamučar; Seyyed Edalatpanah (International Journal of Research in Industrial Engineering)
The current study investigates to characterize the Complex Programming Problem (CPP) solution in a fuzzy environment. The paper is divided into two parts: 1) the first presents a Fuzzy Complex Programming Problem (F-CPP) with fuzzy complex constraints, and 2) the second presents the optimality criteria using the fuzzy complex cone. The CPP is suggested by involving fuzzy numbers in the constraints in parts. Using the cut set concepts, the problem is converted into the complex programming. A number of basic theorems with proofs are established concerning the basic results for the fuzzy complex set of solutions for the F-CPP, and the optimality criteria of the saddle point for F-CPP with fuzzy cones is derived.